1998
DOI: 10.1111/j.1365-2672.1998.tb05273.x
|View full text |Cite
|
Sign up to set email alerts
|

Note: Characterization of Vibrio cholerae O139 Bengal isolated from water in Malaysia

Abstract: R. SON, G. RUSUL, L. SAMUEL, YUHERMAN, S. SENTHIL, A. RASIP, E.H. NASRELDIN AND M. NISHIBUCHI. 1998. Four Vibrio cholerae O139 Bengal strains isolated from surface water were characterized by antibiotic resistance, plasmid profile, presence of cholera toxin gene and random amplification of polymorphic DNA (RAPD) analysis. All four strains exhibit multiple resistance towards the antibiotics tested with a multiple antibiotic resistance index of 0·5–0·66, and harboured a 2·0 MDa non‐conjugative plasmid. The Vibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The results of the ERIC-PCR fingerprint profiles supported the results obtained by ribotyping that multiple clones of V. cholerae O139 were present in the aquatic environment. These observations are in agreement with those of others who demonstrated heterogeneity in O139 V. cholerae strains (10,17,20,29).…”
Section: Eric-pcrsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of the ERIC-PCR fingerprint profiles supported the results obtained by ribotyping that multiple clones of V. cholerae O139 were present in the aquatic environment. These observations are in agreement with those of others who demonstrated heterogeneity in O139 V. cholerae strains (10,17,20,29).…”
Section: Eric-pcrsupporting
confidence: 83%
“…It was found recently that a highly epidemic form of cholera-like disease on the Indian subcontinent was strongly associated with non-O1 strains of V. cholerae designated V. cholerae O139 Bengal (1,21,25), which subsequently spread to the different parts of the world (1,6,11). Studies of V. cholerae from environmental surface water indicated that O139 Bengal, like O1 vibrios and non-O1, non-O139 vibrios, may survive better in the aquatic environment in association with aquatic plants (13,14,26) and that environmental water may be a reservoir for infectious V. cholerae O139 (14,29).…”
mentioning
confidence: 99%
“…The 20 toxigenic strains were isolated from various kinds of seafoods collected at various locations in Malaysia (Table 1). This result and the isolation of toxigenic O139 strains from seawater in Malaysia in 1996 (38) suggest that the aquatic environment may serve as the reservoir for toxigenic V. cholerae in Malaysia.…”
Section: Resultsmentioning
confidence: 91%
“…An El Tor O1 Inaba strain isolated from a patient during an outbreak in Sarawak, Malaysia, in 1998 was provided by Patrick Benjamin Guda Miri of the General Hospital, Miri, Sarawak. Toxigenic O139 strains isolated from seawater in Malaysia in 1996 were described previously (38). Other V. cholerae O1 Ogawa strains isolated from international travelers arriving in Japan from various Asian countries between 1982 and 1998 were supplied by Osaka Airport Quarantine Station, Kansai Airport Quarantine Station, and Nagoya Airport Quarantine Station, Japan.…”
Section: Methodsmentioning
confidence: 99%